2020
DOI: 10.17576/jkmjc-2020-3603-13
|View full text |Cite
|
Sign up to set email alerts
|

Discourse Network of a Public Issue Debate: A Study on Covid-19 Cases in Indonesia

Abstract: This research is intended to answer the question of the discourses developed in association with Covid-19 management. Discourse in this regard is understood within the context of public policy, i.e. a set of concepts or ideas conveyed by actors to influence public policies. This study employed a discourse coalition theory. In addition, this study applied a discourse network analysis (DNA) method, combining discourse analysis (qualitative contents) and social network method. The DNA method maps any developing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 8 publications
(12 reference statements)
0
14
0
9
Order By: Relevance
“…From the aspect of communication during the Covid-19 pandemic, Eriyanto and Ali (2020) show that the Indonesian government seeks to present discourse to dominate public conversations and conduct adjustments to mediate conflicting discourses. Another study conducted by Olimat (2020b) analyzed dysphemism in Trump's Covid-19 speeches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the aspect of communication during the Covid-19 pandemic, Eriyanto and Ali (2020) show that the Indonesian government seeks to present discourse to dominate public conversations and conduct adjustments to mediate conflicting discourses. Another study conducted by Olimat (2020b) analyzed dysphemism in Trump's Covid-19 speeches.…”
Section: Introductionmentioning
confidence: 99%
“…Because the government's ineffective communication during the Covid-19 pandemic can lead to confusion, misunderstanding and bring social impacts on the citizens as well as prolong the pandemic period (Kim & Kreps, 2020). Studies by Eriyanto and Ali (2020) and Olimat (2020b) established that studies on how the government employed discursive strategies to inspire the citizens have not been researched, while Kim and Kreps's study (2020) demonstrated that research on the language used by the government in communication during the Covid-19 pandemic is timely, although studies such as Kim and Kreps (2020) and Rajandran (2020) have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…These biases are hidden behind the claims of neutrality, objectivity, and impartiality that the media speaks eloquently to the public. (Eriyanto & Ali, 2020) In addition, the direct and indirect involvement of media owners in practical politics (either as party elites, sympathizers, or affiliations with government officials) also has a major influence on the media. In the context of journalism, the influence of media owners directly or indirectly is considered to have an impact on biased texts and visuals.…”
Section: Discussionmentioning
confidence: 99%
“…Discourse is composed of many parts. According to Hajer (1993 in (Eriyanto, 2020)), discourse consists of a collection of ideas, conceptions, concepts, and categories that are formed via certain behaviors and then applied to the world to give it meaning. The following topics are brought into sharper light by this definition: Discourse is an "assemblage of ideas, thoughts, or concepts"; discourse is created, reproduced, and modified by social actors; discourse is constructed by actors who have a stake in how others interpret reality; and discourse is bounded and restricted to specific social contexts (Eriyanto, 2020).…”
Section: Introductionmentioning
confidence: 99%